2014
DOI: 10.1186/s13012-014-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a rapid response mechanism to meet policymakers' urgent needs for research evidence about health systems in a low income country: a case study

Abstract: ObjectivesDespite the recognition of the importance of evidence-informed health policy and practice, there are still barriers to translating research findings into policy and practice. The present study aimed to establish the feasibility of a rapid response mechanism, a knowledge translation strategy designed to meet policymakers' urgent needs for evidence about health systems in a low income country, Uganda. Rapid response mechanisms aim to address the barriers of timeliness and relevance of evidence at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 29 publications
2
103
0
1
Order By: Relevance
“…[307][308][309][310] Whereas international agencies are increasingly investing in research in Africa, they rarely provide core funding to strengthen institutions involved in such research. In addition, caps on overheads by some western research funders for African research institutions limit institutional development.…”
Section: The Need For Investment In Health Research and Institutionalmentioning
confidence: 99%
“…[307][308][309][310] Whereas international agencies are increasingly investing in research in Africa, they rarely provide core funding to strengthen institutions involved in such research. In addition, caps on overheads by some western research funders for African research institutions limit institutional development.…”
Section: The Need For Investment In Health Research and Institutionalmentioning
confidence: 99%
“…Surprisingly, despite the reported importance of EIHP, majority of the participants in this study, used evidence only sometimes with only a few who used evidence all the time when making decisions. Similarly, Mijumbi and colleagues [16] reported that, all the policymakers affirmed that research evidence was an important part of the policymaking process. This confirms the important of using research evidence in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, researcher like Lavis and colleagues [8] reported that policy makers were not supported to acquire the required skills or to use research evidence in different forms. In addition, Mijumbi and others [16] indicated a lack of experience in RRM among policy makers and thus addressing this problem through such mechanisms and if accepted by policymakers can go a long way in improving capacity of policy makers in using RRM services. Thus, capacity building is also seen as important to increase researchers' abilities to produce and effectively disseminate evidence of use to decision makers [10] and to improve policy makers' abilities to critically appraise and interpret these outputs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers piloted a rapid response service in March 2010, providing rapid response briefs on demand to policymakers in Uganda [17]. The objectives of this study were to (1) explore Ugandan policymakers’ experiences with a rapid response brief template developed for this service; (2) use our findings to improve the format of that template; and (3) assess the extent to which the revised rapid response brief template better met policymakers’ needs.…”
Section: Introductionmentioning
confidence: 99%